2010
DOI: 10.1177/0974686220100202
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Structure and Performance of Indian Companies

Abstract: This study investigates the relationship between corporate governance structure and performance of Indian companies. The main objective of this study is to examine the impact of selected board characteristics and ownership structure on the firm performance. This analysis ranges over a period of six years, from 2001-02 to 2006-07 and is based on Pharmaceutical and IT industry. Least square dummy variable regression model has been used to study the relationship. We find that while board size, listing status of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, on the other hand, the ESG negatively affected the operational, financial and market performance in the banking sector. Dalal and Thaker (2018) examined the impact of ESG factors on the performance of Indian Public Limited companies in terms of profitability and firm's value. It was found that good corporate ESG performance enhances financial performance assessed through accounting as well as market-based measures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, on the other hand, the ESG negatively affected the operational, financial and market performance in the banking sector. Dalal and Thaker (2018) examined the impact of ESG factors on the performance of Indian Public Limited companies in terms of profitability and firm's value. It was found that good corporate ESG performance enhances financial performance assessed through accounting as well as market-based measures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It was also found that credit ratings and ESG disclosure were forming a circular relationship with each other and credit ratings of a firm significantly impacted the overall reporting of ESG and even the extent of ESG component disclosure. Dalal and Thaker (2019) conducted their study on 65 Indian firms listed on the NSE 100 ESG database from 2015–2017 to examine the ESG influence on the financial performance of these listed firms; they concluded that the financial performance of a firm enhanced positively by its good corporate ESG performance. A study conducted by Vyas et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The acceptance of ESG's financial materiality in the investments is evident in the literature available. A good sum of studies shows the ESG's positive impact on the valuation (Dalal and Thaker, 2019; Fatemi et al. , 2018; Nekhili et al.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptance of ESG's financial materiality in the investments is evident in the literature available. A good sum of studies shows the ESG's positive impact on the valuation (Dalal and Thaker, 2019;Fatemi et al, 2018;Nekhili et al, 2021). However, a few studies contradict this and find signs of no impact of firm's ESG on the valuation (Velte, 2017;Cordazzo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%